Mechanical Performance Analysis of Geopolymer Concrete using Fly Ash Tanjung Jati B for Sustainable Construction Materials - Bobby Rio Indriyantho; Purwanto Purwanto; Rydell Riko (Diponegoro University, 2023)
The use of concrete as the primary building construction material caused serious problems in the construction industry. Concrete is not regarded as an environmentally friendly material since the use of cement results in high carbon emissions during the manufacturing process. One effort to replace cement without reducing concrete strength is to use fly ash as a concrete ingredient, which is known as geopolymer concrete. The goal of this research was to determine the basic mechanical properties of geopolymer concrete and compare it to conventional concrete with the same material proportions. The mix design of the three different proportions with the ratio of aggregates to binder as 70% : 30%, 60% : 40% and 50% : 50% was maintained such that the concrete mix has a good workability. As a result, the so-called workable fly ash-based geopolymer concrete has higher compressive strength, splitting tensile strength, and modulus of elasticity compared to conventional concrete, while its Poisson's ratio is slightly lower.